2019
DOI: 10.3390/ma12152435
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration Using a Three-Dimensional Hexahedron Channeled BCP Block Combined with Bone Morphogenic Protein-2 in Rat Calvarial Defects

Abstract: It is important to obtain sufficient bone mass before implant placement on alveolar bone, and synthetic bone such as biphasic calcium phosphate (BCP) has been studied to secure this. This study used a BCP block bone with a specific structure of the three-dimensional (3D) hexahedron channel and coating with recombinant human bone morphogenetic protein-2 (rhBMP-2) impregnated carboxymethyl cellulose (CMC) was used to examine the enhancement of bone regeneration of this biomaterial in rat calvarial defect. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Several studies have confirmed that the block-type BCP is efficient in maintaining space [36]. Although alloplastic block bone shows lower bone formation than that obtained using autologous block bone [37], the former shows superior bone formation compared to that observed in the absence of grafts [36]; additionally, it has been reported that greater bone formation is observed when rhBMP-2 is added [38]. In addition, the block-type BCP exhibits superior bone regeneration ability compared to that of the particle type [39], and the use of block-type BCP is reported to be advantageous for barrier membrane support [40].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have confirmed that the block-type BCP is efficient in maintaining space [36]. Although alloplastic block bone shows lower bone formation than that obtained using autologous block bone [37], the former shows superior bone formation compared to that observed in the absence of grafts [36]; additionally, it has been reported that greater bone formation is observed when rhBMP-2 is added [38]. In addition, the block-type BCP exhibits superior bone regeneration ability compared to that of the particle type [39], and the use of block-type BCP is reported to be advantageous for barrier membrane support [40].…”
Section: Discussionmentioning
confidence: 94%
“…D) NC specimen with moderate bone neoformation (*) coming from the margins of the defects and predominance of fibrous connective tissue (green arrows) in the center (all figures Masson's trichrome; original magnification ×20; yellow arrows = defect edges) the osteoconduction capability of a biphasic calcium phosphate (BCP) ceramic composed of hydroxyapatite and βtricalcium phosphate, found a maximum percentage of 74.22% ± 25.39% of newly formed bone in 7 mm defects at 60 days, when the graft was covered with a bovinederived collagen membrane. Finally, even using a 3D scaffold of biphasic calcium phosphate coated with recombinant human bone morphogenetic protein-2 (rhBMP-2), only 33.79% ± 3.66% of newly formed bone was reported within 8 mm critical defects by Kim et al 38 after 4 weeks of healing.…”
Section: F I G U R Ementioning
confidence: 99%
“…Several studies in which μCT was used to assess the repair of critical defects have shown that this method confirms and validates histomorphometric findings, besides adding relevant information such as bone mineral density, bone mineral content and bone volume. 26,38,39,[45][46][47][48][49][50] The inclusion of immunohistochemical analysis for bone resorption and neoformation markers in earlier periods of healing could also contribute to the understanding of the biological phenomena that may explain the behavior of demineralized autogenous bone as a graft material.…”
Section: F I G U R Ementioning
confidence: 99%
“…2,7 Further, it is difficult to use for the narrow orifice of bone defect and difficult to fill fully without empty space. 12,13 Dong Jin, Ryu and Eui Yub, Jung contributed to this article equally.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is widely used in clinical practice, previous BCP products have problems of low‐compression strength, 11 rejection, and early biodegradation 2,7 . Further, it is difficult to use for the narrow orifice of bone defect and difficult to fill fully without empty space 12,13 …”
Section: Introductionmentioning
confidence: 99%